Evaluating exposure to and perceptions of the Woolworths Healthy Tuck Shop Guide in Cape Town, South Africa - Marraccini, Toni (Department of Public Health and Family Medicine, 2015)
Both under-nutrition and over-nutrition pose a public health concern, especially for children in South Africa. Several initiatives exist in South Africa in order to promote healthy eating and nutrition at schools. One of them is the Woolworths Making the Difference (MTD) Programme aimed at eliminating barriers to promoting healthy lifestyles that exist at schools, such as the availability of low cost, unhealthy foods either from tuck shops or street vendors. The Healthy Tuck Shop Guide is a recent addition to the MTD programme. The aim of this evaluation is to assess schools’ perceptions of the Woolworths Healthy Tuck Shop Guide as it is being utilized in Woolworths Making the Difference schools.